Staging hydrophilic encounters – experiential methods for creating dialogic listening space. (28th May 2023) - Kitson, Jennifer; Bucknum, Megan; Meenar, Mahbubur
ABSTRACT: This article explores hydrophilia, humans' affective ties with water, through the development of a public storytelling methodology for exploring fluvial senses of place and expanding the fluvial imagination through the art of listening. This 'watershed storytelling' methodology was developed at the confluence of public cultural geographies, the environmental humanities, and oral history in response to calls for greater aesthetic engagement with fluvial landscapes and more inclusive ways of doing oral environmental history. In the absence of tangible bodies of water, we suggest that dialogic listening spaces can generate moments of perceptible feelings of connection, to others and place, through water. We call this affective event a 'hydrophilic encounter, ' we believe it can open empathic capacities to feel, sense, and imagine our interconnectedness through water and place. We share this methodology as one route to publicly facilitate hydrophilic encounters, inviting readers to replicate and adapt this public geography practice within diverse communities interested in engaging public sentiments on the importance of water within regional and global contexts.